GENERATION OF WIND-SERIES USING CUMULATIVE PROBABILITY WIND TRANSITION MATRIX-A FIRST ORDER MARKOV PROCESS - MASCARENHAS, A.; GOUVEIA , A. D.; DESAI, R. G. PRABHU (MAUSAM, 1994)
One appl ica tion ofihe cuuiulative probability wind tra ns ition matrix is 10 determine the various prnhal"lk ....i n,1....-ries th ai mi1;\’hl occur. during the period fur which offs hore oilspil1 risk is 10 be analysed. Du ring th is ;Inalpli ""’t" haw to gene la te different probable "’;110.1 conditions at d iff erent Instances oftime. OnC" ur lhe method s to siumlutcthe nl lhlu m wind behaviourt hrough lime. is 10 U h istorical wi nd da ta presented in the fon n of wi nd Ira n... ilion lItutrix. Th is pa per h it;hli.::hts th r- 1llC’l h(Klulog)’ and use ofthe cumulat ive probability v.i nd transition matrix. in t’lh"ral ill 1111’ ,Iifferl:’nl proba ble wind-series.